2020
DOI: 10.1021/acssuschemeng.9b06026
|View full text |Cite
|
Sign up to set email alerts
|

Novel Postcombustion Capture Process for CO2 from the Flue Gas of Coal-Fired Power Plants Using a Green Deep Eutectic Solvent

Abstract: Green, efficient, and low energy consumption capture of CO 2 from the flue gas of coal-fired power plants has been one of the most popular research topics in the world. In this work, a concept process of postcombustion capture (PCC) using a choline chloride/urea (1:2) deep eutectic solvent (DES) as a physical solvent was proposed. The DES-based PCC process is modeled and simulated using commercial Aspen Plus simulation software. The required parameters were studied and further embedded in Aspen Plus. The simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…Process Design and Optimization. On the basis of the research of Wang et al, 43 the process flow sheet of the DESbased PCC CO 2 capture is shown in Figure 8. As shown in Figure 8, the flue gas first enters the separator to remove water, and then the dehydrated flue gas is mixed with the gas from the flash tank (Flash1) and enters the multistage compressor (MCompr, five stages) together to be compressed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Process Design and Optimization. On the basis of the research of Wang et al, 43 the process flow sheet of the DESbased PCC CO 2 capture is shown in Figure 8. As shown in Figure 8, the flue gas first enters the separator to remove water, and then the dehydrated flue gas is mixed with the gas from the flash tank (Flash1) and enters the multistage compressor (MCompr, five stages) together to be compressed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is due to the fact that low pressure causes a large desorption of CO 2 , affecting the recovery rate of CO 2 , while high pressure causes insufficient O 2 and N 2 desorption, influencing the purity of CO 2 in the product gas. 43 Therefore, the pressure of Flash1 is set to 10 bar to meet the requirements: namely, a purity of CO 2 in the product gas of >90% and a recovery rate of CO 2 of >90%. In contrast to the pressure, as shown in Figure 10b, low temperature leads to insufficient CO 2 and N 2 desorption, while high temperature causes a large desorption of CO 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial design with the equilibrium model for the DDC shows that the calculated diameter for the first part of the column is 1.23 m, while the second part is 1.78 m. Of course, the obtained values for the diameter of each part are used as the first estimate in the non-equilibrium model. Consequently, the new values of diameters are corrected and get closer to the real industrial values using the nonequilibrium model[31][32][33][34]. The mechanical specifications of the DDC for the first and second parts of the column are presented in rows 4-10 and 4-8 of Tab.…”
mentioning
confidence: 99%